Enhancement of the immunogenicity of an infectious bronchitis virus DNA vaccine by a bicistronic plasmid encoding nucleocapsid protein and interleukin-2 - Tang, Mengjun (J Virol Methods, 2008)
A DNA vaccine against infectious bronchitis virus (IBV) can induce specific humoral and cell-mediated immunity. However, compared to conventional vaccines, DNA vaccines usually induce poor antibody responses. To develop a more potent IBV DNA vaccine formulations, a monocistronic vector encoding the nucleocapsid protein of IBV and a bicistronic vector separately encoding the nucleocapsid protein and immune-stimulatory interleukin-2 were constructed. When the DNA vaccines were administered to the quadriceps muscle of chickens, the induced humoral and cellular responses were evaluated. There was a significant difference in ELISA antibody levels elicited by either monocistronic or bicistronic DNA vaccines. The percentage of CD3(+), CD3(+)CD8(+) and CD3(+)CD4(+) subgroups of peripheral blood T-lymphocytes in chickens immunized with bicistronic DNA vaccine were higher than those in chickens immunized with monocistronic DNA vaccine. When chickens were challenged with a virulent strain of IBV, the protective efficacy could be enhanced significantly after immunization with bicistronic DNA vaccine. These results demonstrated that bicistronic DNA vaccine is an effective approach to increase IBV DNA vaccine immunogenicity.